MENUJU SUSTAINABILITY DENGAN TRI HITA KARANA (SEBUAH STUDI INTERPRETIF PADA MASYARAKAT BALI) - Hasudungan Hutasoit; Redaktur Wau (Business Management Journal, 2017)
This article aims to provide an understanding of the meaning of the local wisdom of Tri Hita Karana (THK) of Bali as a concept to achieve sustainability. THK relevant issues was appointed amid the deterioration of the quality of life of mankind as a result of excessive exploitation of nature. That downturn has also hit Indonesia due to the hegemony of positivist paradigm and tendencies attributing a materialistic rationality. Indeed in THK there are values that ought to be executed to achieve sustainability. If the corporate world to apply to achieve Triple Bottom Line sustainability, Balinese prove THK has been keeping sustainable remains until now Bali. The difference of the two is on the concept of profit (profit) and Lord's (parahyangan). This research combines the data gathering methods Cresswel, ethnographic interviews Spradley and qualitative paradigm analysis interpretivisme.Keywords: Interpretivisme, Tri Hita Karana, Sustainability and Antropological Approach.